Front Cover Image, Volume 87, Issue 2, February 2020. Issue 2 (24th February 2020) - Sharma, Sachin; Kumaran, Girishkumar K.; Hanukoglu, Israel
Abstract : Front Cover Caption : The cover image is based on the Research Article High‐resolution imaging of the actin cytoskeleton and epithelial sodium channel (ENaC), CFTR and aquaporin‐9 localization in the vas deferens by Sachin Sharma et al., https://doi.org/10.1002/mrd.23317 . Credit: Cover image © Sachin Sharma and Israel Hanukoglu Images.